Teori Khudi Perspektif Muhammad Iqbal: Analisa Terapi Holistik Mengatasi Obsessive Compulsive Disorder - Yasrif, M. Ali; Arroisi, Jarman (UIR Press, 2025)
Modernization and materialism increasingly dominate daily life, making it difficult for individuals to find spiritual and emotional balance. This study investigates Muhammad Iqbal's Khudi theory within Islamic psychology and its application to modern psychological issues, particularly OCD. Using a qualitative literature-based approach and Spradley's analytical model, including Domain Analysis, Taxonomy Analysis, Componential Analysis, and Cultural Theme Analysis, the research leads to three key conclusions. First, traditional psychological methods often fall short in addressing the existential and spiritual aspects of mental health crises, especially in disorders like OCD. Second, applying Iqbal's khudi principles-focusing on self-development, self-understanding, and spiritual growth-provides a holistic approach that effectively aids individuals in managing obsessions and compulsive behaviors. Third, incorporating khudi principles such as love, faqr, courage, tolerance, and personal honor into OCD therapy yields significant benefits. Love and personal honor enhance self-esteem and dignity, while faqr reduces reliance on rituals. Courage and tolerance enable individuals to accept imperfections, thereby decreasing anxiety and improving overall emotional and spiritual well-being.